A new selective medium for Streptococcus pneumoniae. Issue 8 (August 1980) - Nichols, T; Freeman, R
Abstract : The development and evaluation of a new selective medium for Streptococcus pneumoniae is described. It is shown that the new medium (crystal violet-nalidixic acid-gentamicin agar:CVNG) is highly selective for Strep. pneumoniae in sputum specimens containing other organisms and is also sensitive, being only marginally inhibitory when compared to Columbia blood agar. The advantages of the medium in routine use are presented, based on 206 consecutive sputum specimens. It is concluded that CVNG medum is a useful adjunct to sputum bacteriology, especially in combination with digestion of the sputum samples by Cleland's reagent.